A Possible Genotype-Phenotype Correlation in Ashkenazi-Jewish Individuals With Aicardi-Goutières Syndrome Associated With SAMHD1 Mutation. (March 2015) - Straussberg, Rachel; Marom, Daphna; Sanado-Inbar, Esther; Lakovsky, Yaniv; Horev, Gadi; Shalev, Stavit A.; Lev, Dorit; Lerman-Sagie, Tally; Leshinsky-Silver, Esther
Aicardi-Goutières syndrome is a genetic neurodegenerative disorder with clinical symptoms mimicking a congenital viral infection. Mutations in 6 genes are known to cause the disease: 3 prime repair exonuclease1, ribonucleases H2A, B, and C, SAM domain and HD domain 1, and most recently ADAR1 . HD domain 1 mutations were previously reported in the Ashkenazi-Jewish community. We report an additional patient of Ashkenazi-Jewish descent and review the other 3 cases affected with Aicardi-Goutières syndrome due to SAM domain and HD domain 1 ( SAMHD1 ) mutations described in Israel. We propose that there may be a phenotypic-genotypic correlation in accordance with the type of mutations inherited in the SAMHD1 genotype and suggest that Aicardi-Goutières syndrome may not be a rare disease in the Ashkenazi-Jewish population.